Lean Entrepreneurship Innovation in the modern enterprise - George Watt; Abrams, Howard (Canada CA Press, 2022)
Utilize this comprehensive guide in your organization to create a corporate incubator that protects innovative ideas from oppressive corporate processes and culture and gives those ideas the resources and environment they need to grow and have the best possible chance to thrive.Innovation is hard. Ironically, innovation in a large enterprise can be even more difficult. Policies designed for mature businesses often crush emerging businesses along with the entrepreneurial spirit of the innovators. Procedures can make it difficult, even impossible, for innovative employees to get their ideas funded, or even seen. As a result, even companies with their roots in innovation can find themselves unable to innovate, with a devastating impact on employee morale and often resulting in the exodus of the most creative employees.In Lean Intrapreneurship the authors leverage decades of personal experience innovating in large enterprises to explore the root causes of failure to innovate in established organizations, and offer a solution to the innovator$1 (Bs dilemma. The book includes a recipe for creating a repeatable program for innovating in large organizations, including tools, tips, and strategies developed by the authors as they created an innovative incubation program for a multi-billion-dollar technology company. It also offers a wealth of information to help aspiring intrapreneurs and entrepreneurs bring their ideas to life.s
Keywords: Executive management